HUBUNGAN PARITAS DENGAN KECEMASAN IBU BERSALIN DI KELURAHAN KIJANG KOTA KABUPATEN BINTAN - Anastasia Susanti; Norma Jeepi; Mawardi Badar (Universitas Batam, 2023)
Anxiety occurs because of feelings of worry about childbirth. pregnant women for the first time are worried, while mothers who have been pregnant before feel not worried. This study aims to determine the relationship between parity and maternal anxiety in the Kijang Village, Bintan Regency. The research method is a correlation descriptive design with a cross sectional design. The population of this study were all mothers giving birth in Kijang Village, Bintan Regency. A sample of 33 women giving birth was taken by purposive sampling. Data analysis using Chi-Square (α 0.05). The results showed that the majority of respondents did not experience anxiety, namely 22 (66.7%) respondents, of which 11 (100%) respondents were multiparous and 11 (100%) respondents were grandemultipara. there is a relationship between parity and maternal anxiety in the Kijang Village, Bintan Regency City.